Managing waste and cost in the construction industry: A case study of the road construction industry - Sagoe, Augustine (2012)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Commonwealth Executive Master of Business Administration, October, 2011